Hubungan Kebiasaan Merokok Dengan Tekanan Darah - Yuliaus Angga; Yunus Elon (Jurnal Kesehatan Komunitas, 2021)
Blood pressure is one of the vital signs that can provide an overview of a person's health status. One of the factors that can affect blood pressure is smoking. The purpose of this study was to analyze smoking habits with blood pressure in adult men in Sebunga Village, Sambas Regency, West Kalimantan. This study used a correlational design with a cross-sectional analytic study approach. Samples were taken using a non-probability technique, namely convenience sampling. A total of 50 young adult men and young adults, were willing to determine in this study, with informed consent. Bivariate analysis results showed that there was a significant relationship between smoking duration and an increase in systolic and diastolic blood pressure p-value <.05. This study concluded, the longer a person smoked, the higher the risk for experiencing increased blood pressure.